PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN BERBASIS SAK EMKM MELALUI APLIKASI LAMIKRO DI UMKM TAS KULIT SALSABILA - Dwijayanti, Ayu; Pradipa, Nyoman Angga; Utami, Ni Made Mega Abdi; Suarbawa, Ketut Gde Juli (Jurnal Abdi Insani, 2024)
Salsabila MSMEs in managing their business have serious problems related to the lack of consistent financial records. Initial communication activities with partners, obtained information that MSME partners also do not separate personal and business finances, the finances made are still limited to recording profits so that they do not comply with applicable standards. Community service activities (PKM) have the aim of strengthening the understanding of MSMEs about the importance of preparing financial reports according to applicable standards, namely SAK EMKM. PKM is focused on the owner and 4 employees of Salsabila MSMEs. Problem solving solutions by conducting training and assistance in preparing SAK EMKM-based financial reports through the LAMIKRO application. The mentoring method consists of providing material through lectures, exposure to basic concepts and practical exercises for inputting transactions in the LAMIKRO application. Monitoring and evaluation indicated that the LAMIKRO training was understood by almost 85%. MSME actors have the perception that accounting training through LAMIKRO makes it easier to record business transactions. Real results in the field also show that 80% of partner MSMEs have been able to prepare standard financial reports independently and understand information from financial reports for business decision making.